Mayflies (Ephemeroptera) from Reserva Ecológica Michelin, Bahia, Brazil. Issue 4 (1st October 2016) - Campos, Rogério; Mariano, Rodolfo; Calor, Adolfo R.
ABSTRACT: New records and distributional notes are provided for Reserva Ecológica Michelin, an Atlantic Forest fragment near the southern coast of Bahia State, Brazil. Two families, four genera and five species are recorded for the first time in Bahia State. Additionally, one family, two genera and three species are also recorded for the first time in the Northeast Region of Brazil, resulting in nine families, 48 genera and 96 species recorded to this region. Amongst the recorded species, Hermanella mazama (Nascimento, Mariano, and Salles, 2012) has been classified as an endangered species on the official Brazilian red list.